Protein dan vitamin D3 meningkatkan kadar fosfor maksila anak tikus putih Rattus novergicus galur Wistar dengan berat badan lahir rendah - Hidayah, Rizki Amalia; Huriyati, Emy; Hanindriyo, Lisdrianto (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Protein and vitamin D3 increase the phosphorus levels of maxillary in malnourished mice pupBackground: Protein deficiency during pregnancy leads to malnutrition in the newborn. One of the signs is low birth weight, which impacts bone and teeth growth problems, most probably related to vitamin D and phosphorus deficiency. Adequate protein and vitamin D3 during the nursing period increase the phosphorus level of bone related to fosfor absorption, which increases in the gut.Objective: This research was conducted to determine the effect of protein and vitamin D3 during the nursing period on increasing phosphorus levels of maxillary in prenatal malnutrition mice.Methods: Experimental study with post-test-only control group design. Thirty the Rattus novergicus Wistar strain mice were divided into five groups (n=6). The positive control group (healthy mice suckle in mother who received a standard protein diet and vitamin D3 0.36 IU/g BW/day/oral), negative control group (malnourished mice suckle in mother who received a low protein diet), and three groups of malnutrition mice suckle in mother who receives intervention standard protein diet with vitamin D3 0.36 IU/g BW/day/oral, low protein diet with vitamin D3 0,36 IU/g BW/day/oral, and a standard protein diet without vitamin D3. The parameter measured was phosphorus levels in the maxillary.Results: ANOVA test results showed significant phosphorus level differences of maxillary between groups (p<0.001), and the Post Hoc test showed differences between the control group with interventions 1, 2, and 3 groups.Conclusion: Intervention of a standard protein diet without vitamin D3 or a low protein diet with vitamin D3 0.36 IU/day/oral significantly increases the phosphorus level of maxillary in malnourished mice. However, combining a standard protein diet and vitamin D3 0.36 IU/day/oral is the most optimum for improving maxillary bone phosphorus levels in malnourished mice.